THE MYTH OF MOUNT PADANG BY COMMUNITY PERSPECTIVELOCAL AND ITS EFFECT ON THE POWER OF TOURISM ATTRACTIONS - Hariwanto, Army Tunggu (Journal of Indonesian Tourism and Policy Studies, 2020)
The Gunung Padang site is one of the megalithic cultural heritage sites in West Java. Precisely located in the hamlet of Gunung Padang and Panggulan, Desa Karymukti, Kecamatan Campaka, Kabupaten Cianjur. The Gunung Padang site is inseparable from myths where myths developed in the local community and referring to local wisdom in the Priangan area alleged that this site is a place of worship of ancestral spirits, gods and fulfilling spiritual needs in the past. The existence of the site and the community around the Gunung Padang site has a role to revive the myth so that it becomes a value on the Gunung Padang site. In addition to living the myth, the local community also maintains that the physical building of the site is maintained and maintained. Values related to myths and local communities are formed through perceptions about living myths that provide their own strength for the existence of Gunung Padang which makes this site as a tourist attraction.